2015
DOI: 10.1021/acsami.5b00584
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Mesoporous In2O3 with Enhanced CO Sensing and Photocatalytic Performance: Distinct Morphologies of In(OH)3 via Self Assembly Coupled in Situ Solid–Solid Transformation

Abstract: The present investigation details our interesting findings and insights into the evolution of exotic hierarchical superstructures of In(OH)3 under solvothermal conditions. Controlled variation of reaction parameters such as, reactant concentration, solvent system, crystal structure modifiers, water content along with temperature and time, yielded remarkable architectures. Diverse morphologies achieved for the first time includes (i) raspberry-like hollow spheres, (ii) nanosheet-assembled spheres, (iii) nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…In addition, SEM observations also reveal that hollow Cr-doped WO 3 microspheres were assembled in a more complex manner (Figure d and Figure S2b). These findings corresponding to the related publications, which confirm that Cr-doped WO 3 hierarchical surface and mesoporous morphology well promote the diffusion and transport of gases into sensing layer, thus obtaining better sensor performance.…”
Section: Resultssupporting
confidence: 85%
“…In addition, SEM observations also reveal that hollow Cr-doped WO 3 microspheres were assembled in a more complex manner (Figure d and Figure S2b). These findings corresponding to the related publications, which confirm that Cr-doped WO 3 hierarchical surface and mesoporous morphology well promote the diffusion and transport of gases into sensing layer, thus obtaining better sensor performance.…”
Section: Resultssupporting
confidence: 85%
“…To date, significant amount of research studies have been reported on the sensing of CO gas (Table S1, ESI †). First, very high sensor responses, in the range of 29-480, was attained by means of using various material systems, including Au and SnO 2 nanocrystals on CNTs, 18 Co 3 O 4 nanowires, 19 In 2 O 3 raspberry hollow spheres, 20 Au-doped SnO 2 -In 2 O 3 nanocomposites, 21 Pt/SnO 2 , 22,23 and Sm 2 O 3 -doped Pt/SnO 2 . 23 However, the concentration of CO gas was set to 100-1000 ppm.…”
mentioning
confidence: 99%
“…InOOH is a metastable oxide; therefore, the phase transformation of In(OH) 3 to InOOH is a non-equilibrium system. However, as shown in the TGA curve of In(OH) 3 in Figure 2, the weight loss in the temperature range of 50-150°C is slow with a weight loss rate is about 2.41%, which corresponds to the physical evaporation of adsorbed water on the sample surface (Shanmugasundaram et al, 2015). e weight loss rate is 2.97% in the temperature range of 150-200°C, which is due to the chemical dehydration of In(OH) 3 [2In(OH) 3 =2InOOH+H 2 O].…”
Section: Phase Structurementioning
confidence: 97%